Lupus and NMOSD: The Blending of Humoral Autoimmunity - Maria Goretti S. Ochi; Samantha C. Shapiro; Esther Melamed (Case Reports in Rheumatology)
Systemic lupus erythematous (SLE) is a chronic autoimmune disease that can target any organ of the body. It may coexist with other autoimmune neurologic conditions such as neuromyelitis optica spectrum disorder (NMOSD). NMOSD, previously known as Devic’s disease, is an autoimmune inflammatory disorder of the central nervous system (CNS) that targets the spinal cord, optic nerves, and certain brain regions. Most current evidence suggests that NMOSD is best described as a CNS astrocytopathy. While these diseases share several immunosuppressive treatment options, timely diagnosis of NMOSD is critical as patients may benefit from treatment tailored specifically to NMOSD as opposed to SLE. Steroids, plasmapheresis, intravenous immunoglobulin, cyclophosphamide, azathioprine, mycophenolate mofetil, and rituximab are used to treat both SLE and NMOSD. However, there are several new therapies (inebilizumab, eculizumab, and satralizumab) recently approved specifically for use in NMOSD. In this case series, we report on three patients with coexisting SLE and NMOSD. We describe a 31-year-old woman who suffered an NMOSD flare after 11 years of clinical remission in the context of receiving an influenza vaccination; her SLE remained quiescent on hydroxychloroquine. Next, we describe a 52-year-old woman with emergence of neurologically devastating seropositive NMOSD in the setting of active treatment for SLE with intravenous cyclophosphamide, oral steroids, and hydroxychloroquine. Last, we describe a 48-year-old woman with emergence of seronegative NMOSD in the setting of SLE that was well-controlled on azathioprine and hydroxychloroquine. These cases illustrate the importance of accurate diagnosis and targeted treatment of NMOSD when coexisting with SLE.